THE USING OF EMOTICON IN BBM STATUS - Sholihatul Hadimah Daulay (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2016)
Emotion is the feeling which felt by someone in facing specific situation.Semantically, someone who has the emotion is called as the doer. Emotions involve the change of facial expression, so that it can reflect one's emotions. The emotions of angry, sad, happy, scared, and other emotions are often expressed through facial expressions, hand gestures, body, or tone of voice. In BBM status, we always use emoticon to describe our feeling when we do something or feel something, we show our feeling through emoticon. Theuser in BBM use the emoticon when they make status in BBM, the user BBM want their friend in BBM know what they feel and the close friend can give response like the user want.Keywords: Emoticon, BBM